Influence of sintering temperature on dicing performances of metal-bonded diamond blades on sapphire - Mian Li; Jiawei Liu; Xipeng Xu; Dekui Mu (Journal of Materials Research and Technology, 2024)
A novel Ti–Al-Diamond metal matrix composite (MMC) material has been recently developed for fabricating diamond blade that is an indispensable tool for the mechanical dicing of optoelectronic devices. This work aims to achieve a deep understanding of the influence of sintering temperature on the microstructure, the mechanical and frictional properties, and the grinding and dicing performances on hard-and-brittle materials. Firstly, the microstructures and the mechanical and frictional properties of Ti–15Al-25 vol% Diamond metal matrix composites (MMCs) sintered at 750, 850, and 950 °C were investigated. The upraising of sintering temperature results in the enhancement of the diffusion between constitute elements, which consequently increases the hardness and bending strength, but reduces the porosity of sintered MMCs. Then, Ti–15Al-25 vol% Diamond blades were sintered at 750, 850, and 950 °C for dicing of sapphire. The increase in sintering temperature was found to be responsible for the compromise of the self-sharpness capability of diamond blades, resulting in an inferior dicing quality in terms of the chipping size, the kerf width, and the surface roughness, but an improved dicing ratio. Results obtained in this work indicate that sufficient porosity and self-sharpening capability play the most determinant role in satisfying the dicing quality of sapphire.